Tahfidz Al-Quran dan Kecerdasan Spiritual Santri Dalam Perspektif Tafsir An-Nur Prof. Hasbi Ash-Shiddieqy - Abdillah, Imam Ahmad Abi; Arifin, Zainal; Is, Fadhilah (Jayapangus Press, 2025)
Memorizing the Quran is not only a noble form of worship, but is also believed to have a significant influence on the formation of spiritual intelligence, especially among students of the Ma'had Tahfidz Al-Quran. Spiritual intelligence is a person's ability to understand the meaning of life, have existential awareness, and a deep relationship with God. This study aims to analyze the influence of memorizing the Quran on the formation of spiritual intelligence of students at the Ma'had Tahfidz Al-Quran Imam Ahmad Abi Abdillah with an interpretative approach to Tafsir An-Nur by Prof. T.M. Hasbi Ash-Shiddieqy. The research method used is qualitative-descriptive with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study show that the process of memorizing the Quran contributes greatly to the formation of dimensions of spiritual intelligence of students, such as increasing awareness of the existence of Allah, strengthening moral and ethical values, reflective abilities towards oneself and life, and awareness of divine values ​​in the lives of students. Interpretation of Prof. T.M. Hasbi Ash-Shiddieqy, in his Tafsir An-Nur, emphasized that internalizing Quranic values ​​through memorization can be an effective way to develop a strong spiritual character. The conclusion of this study is that memorizing the Quran is an important medium for developing the spiritual intelligence of Islamic boarding school students as a whole, including aspects of faith, morals, and social sensitivity.